2002
DOI: 10.1021/jp0263931
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Framework Flexibility on the Adsorption Properties of Hydrocarbons in the Zeolite Silicalite

Abstract: Computer simulations of the adsorption of hydrocarbons in zeolites are usually performed using rigid zeolite frameworks. This allows for the use of grid interpolation techniques to compute the hydrocarbon-zeolite interaction very efficiently. In this paper, we investigate the influence of the framework flexibility on the adsorption properties of hydrocarbons adsorbed in the zeolite silicalite. We find that at low loading, the influence of the framework flexibility on the heat of adsorption and the Henry coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
227
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 202 publications
(232 citation statements)
references
References 61 publications
4
227
0
1
Order By: Relevance
“…Each ͑10, 10͒ SWNT within the bundle has a diameter of 13.56 Å, and the carbon atoms were assumed to be rigid and frozen during simulation. Recent study of the adsorption of alkanes in MFI zeolite has revealed that the influence of framework flexibility is quite small, 98 and it is also expected to be so in this work for the low-energy focused equilibrium adsorption.…”
Section: Model and Potentialmentioning
confidence: 88%
“…Each ͑10, 10͒ SWNT within the bundle has a diameter of 13.56 Å, and the carbon atoms were assumed to be rigid and frozen during simulation. Recent study of the adsorption of alkanes in MFI zeolite has revealed that the influence of framework flexibility is quite small, 98 and it is also expected to be so in this work for the low-energy focused equilibrium adsorption.…”
Section: Model and Potentialmentioning
confidence: 88%
“…For molecules that do not have a tight fit in the zeolite framework, the assumption of a rigid zeolite appears to be very reasonable. Indeed, Vlugt and Schenk 215 systematically investigated the effect of flexibility of the zeolite on the adsorption of hexane in MFI and only at high loading could an effect be observed. Of course, a real zeolite is flexible and it might be possible to demonstrate the limitations of the assumed rigidity also for the case of linear alkanes.…”
Section: Flexible Latticementioning
confidence: 99%
“…In our simulations, the zeolites are considered rigid as framework flexibility only results in very small deviations of adsorption properties [45]. For MFI-type zeolite however, a phase transition of the zeolite framework may occur upon Ar adsorption [46,47,48,49,50].…”
Section: Ar Physisorptionmentioning
confidence: 99%